Museums and the challenge of change : old institutions in a new world - Black, Graham (Abingdon, Oxon ; New York, NY : Routledge, 2021)
" 'Museums and the Challenge of Change' explores the profound challenges facing museums and charts ways forward that are grounded in partnership with audiences and communities on-site, online and in wider society. Facing new generations with growing needs and desires, growing population diversity and a digital revolution, the museum sector knows it must change--but it has been slow to respond. Drawing on the expertise and voices of practitioners from within and beyond the sector, Black calls for a change of mind-set and radical evolution (transformation over time, learning from the process, rather than a 'big bang' approach). Internally, a participative environment supports social interaction through active engagement with collections and content--and Black includes an initial typology of participative exhibits, both traditional and digital. Externally, the museum works in partnership with local communities and other agencies to make a real difference, in response to societal challenges. Black considers what this means for the management and structure of the museum, emphasising that it is not possible to separate the development of a participative experience from the ways in which the museum is organised. 'Museums and the Challenge of Change' is highly practical and focused on initiatives that museums can implement swiftly and cheaply, making a real impact on user engagement. The book will thus be essential reading for museum practitioners and students of museum studies around the globe"--
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Social aspects; Museum attendance; Museums and community; Museum visitors; Museums -- Technological innovations